ANALYSIS OF FUNDING AND INVESTATION DECISIONS TO THE VALUE OF COMPANY WITH PROFITABILITY AS MODERATION IN PHARMACY SUB-SECTOR COMPANIES BEFORE AND DURING THE COVID-19 PANDEMIC - Rita Mulyani; Retno Fuji Oktaviani (IAIN Lhokseumawe, 2022)
This study aims to analyze the effect of decisions, funding and investment decisions on the company and analyze the profitability of being able to moderate the effect of funding and investment decisions on the value of the pharmaceutical company sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period, namely before and during the Covid-19 pandemic. Methods The analysis used is multiple regression with R studio tools for statistical data processing. The results showed that the funding decision proxied by DER had no effect on firm value. Investment decisions proxied by PER have an influence on firm value. The profitability variable in this study is able to moderate the effect of investment decisions and decisions on firm value.